The Effectiveness of the Production of Healthy Rice in Comparison with other Rice Varieties in the Upper Northern Region of Thailand - Cheamuangphan, Aree; Singhavara, Montri; Phaoumnuaywit, Aussawin (International Journal of Sustainable Development & World Policy, 2020)
The objective of this study is to examine the efficiency of the production of healthy rice and that of other varieties grown in the upper northern region, by using Meta-Frontier approach in analyzing the rice production efficiency. This study focuses on rice production of farmers by comparing between healthy rice growers and farmers of other rice varieties about 300 and 900 sampling respectively, in the areas of Chiang Mai, Chiang Rai and Phayao. In analyzing the efficiency used one variable of the output, the quantity of rice products and five input variables namely quantity of seeds, cost of soil nourishment fertilizer, cost of weeding, cost of labor in production, and cost of labor for harvesting. The study found that there were more variables for analyzing the efficiency of other rice varieties of rice than those of the healthy rice. Plus, general rice growers had higher production efficiency than healthy rice farmers (0.9439> 0.8604). However, it seems that they should reduce more production factors, particularly labor in production and that in harvesting. Meanwhile, the overall economy of scale had increased while that of each group appeared to be unchanged.